Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Trace element sources, migration and health risks associated with river-groundwater interaction: Insights from isotopes, fluorescence spectroscopy and Monte Carlo simulation - Xu Yang; Muhan Li; Yiying Miao; Fuyang Huang; Zeyuan Liu; Hongli Ma; Ping Miao; Jigang Shi; Zengbao Zhang; Shen Qu; Ruihong Yu (Journal of Hydrology, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Cyclic pulsating pressure enables a self-healable, ultra-stretchable, and super-strong elastomer with tunable mechanical properties - Qian Chen; Haowei Jiang; Weifeng Liu; Junjie Lei; Zhao-Xia Huang; Jin-Ping Qu (Chemical Engineering Journal, 2026)

Ball milling-MnO2 enables viable straw blanket production via lignin depolymerization - Yarong Yang; Zihan Luo; Dingyi Liu; Guoxiang Liu; Zhuoya Zhao; Zifeng Yue; Xuan Wang; Jiaojiao Miao; Ting Xu; Ping Qu; Chuanling Si (Bioresource Technology, 2026)

Information flow reveals three-tiered oceanic drivers of precipitation over the middle–lower Yangtze River Basin - Li-Ying Ning; Dan Wu; Ying Qu; Guo-Lin Feng; Yong-Ping Wu (Climate Dynamics, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Irrigation enhanced nitrification and hydrological partitioning drive groundwater nitrate accumulation in an agricultural irrigation district - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Shen Qu; Dong Qian; Muhan Li; Zeyuan Liu; Ping Miao; Hongli Ma (Journal of Hydrology, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Nitrogen-vacancy-regulated plasmonic Schottky interfaces on Ag/C3N5 for ultrafast oxygen activation and solar-driven antibiotic degradation - Kaizhou Huang; Wei Qu; Tenghui Jin; Yutong Xie; Zhuoyun Tang; Ming Su; Ping Zhang; J. Paul Chen (Chemical Engineering Journal, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Functional characterization of fungal laccases via siRNA silencing enables targeted biodegradation - Jiaqi Sun; Lianyan Yuan; Mengna Niu; Ping Xu; Jinsheng Lin; Cuixin Li; Lin Ma; Huiping Li; Qiang Wang; Shaoxuan Qu (Environmental Pollution, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

miR-574-3p Regulates Smad/Snail Signaling to Promote Epithelial–Mesenchymal Transition in Nasopharyngeal Carcinoma Cells - Ping Ai; Wei Qu; Xianbing Peng; Yi Zeng (Biochemical Genetics, 2026)

Cryoprotective effects and mechanisms of heterologously expressed wheat-derived antifreeze peptide on probiotics - Xiaoge Liu; Jingjing Wang; Yingjing Qu; Long Pan; Xin Wang; Kangyi Zhang; Quan-Ping Liu; Na Liu; Jihong Huang; Ai-Mei Liao (Food Bioscience, 2026)

An ROS-scavenging dual-network hydrogel for diabetic bone regeneration - Zhengyu Cai; Weizhe Xu; Qingxiang Zhang; Xingwu Zhou; Jiang Zeng; Zhiyong Wang; Peng Deng; Ping Sun; Fan Tang; Xing Jiang; Moyuan Qu; Qianming Chen (Chemical Engineering Journal, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Research on anomaly detection and correction method for remote sensing instrument calibration data based on TELSTM-ADC model - Jianhua Qu; Ping Qin; Ling Sun; Weichu Yu; Shengli Wu; Qing Wang; Dongqi Li (International Journal of Remote Sensing, 2026)

Chrysovirus BbCV1 confers enhanced sporulation and environmental fitness to Beauveria bassiana - Lili He; Guogen Yang; Ping Wang; Yang Yang; Jiaojiao Qu; Bo Huang (Pesticide Biochemistry and Physiology, 2026)

In-situ construction of multi-site Co/Co-N-O porous carbons for plasma-catalytic toluene degradation - Chao Cao; Yixin Yang; Guangfei Qu; Rui Xu; Chenyang Zhao; Ping Ning; Junyan Li (Journal of Environmental Chemical Engineering, 2026)

Co-evolution of virulence and drug resistance of transmissible multidrug-resistant hypervirulent Klebsiella pneumoniae in pre-cooked chicken and food-borne health risks - Zheren Wang; Ping Wang; Lijiao Liang; Tianming Qu; Beibei Xu; Ying Chen (International Journal of Food Microbiology, 2026)

Flash-spun composite fiber membranes for broadband electromagnetic absorption and multifunctionality - Daixuan Gong; Xincheng Wang; Meijie Qu; Shuhui Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

Editor's Note to “Factors associated with spatial distribution of severe fever with thrombocytopenia syndrome” [Sci. Total Environ. 750 (2021), 141522] - Ji-Min Sun; Hai-Xia Wu; Liang Lu; Ying Liu; Jiang-Ping Ren; Wen-Wu Yao; Hong-Hua Qu; Qi-Yong Liu (Science of The Total Environment, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

Big data analytics of antibiotic toxicity and inhibition in anammox systems: A review - Xinxin Xu; Meng Zhang; Junwei Wu; Siyu Wang; Wenda Chen; Chifei Dong; Baolan Hu; Ping Zheng; Dan Qu (Bioresource Technology, 2026)

Research on transient fixed-source term for three-dimensional space-time neutron kinetics simulation of hexagonal nodes based on conformal-mapping technique - Haozhe Yang; Chenghui Wan; Jiahe Bai; Ping Qu; Wei Shen (Annals of Nuclear Energy, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Soil texture governs the decoupling of diversity and productivity recovery in restored desert steppe grasslands - Xing Wang; Lei Wang; Nai-ping Song; Wen-jie Qu; Xin-guo Yang (Agriculture, Ecosystems & Environment, 2026)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Synergistic effects of FeCl₃-derived deoxygenation and pore formation on TiFe hydrogen storage alloys - He Zhang; Yong Liu; Guodong Miao; Zhihui Ma; Feng Sun; Aimin Ju; Xuanhui Qu; Ping Li (Chemical Engineering Journal, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Optimizing nutrient management for various potato varieties based on source–sink relationships - Weiyan Wang; Qiying Wu; Xiaojing Qu; Xiya Wang; Jun Zhang; Yu Duan; Ping He (Field Crops Research, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Bimetallic cobalt-cerium loaded copper foam for enhanced paraxylene low-temperature catalytic oxidation: Mechanistic insights and role of oxygen vacancies - Chenyang Zhao; Huanhuan Wu; Guangfei Qu; Yongheng Yuan; Zheng Yuan; Guojun Liu; Zhishuncheng Li; Junyan Li; Yingying Cai; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Design and performance of moisture-responsive piezoelectric nanogenerators based on electrospinning poly(vinylidene fluoride) films - Shuhui Li; Meijie Qu; Yonghao Chen; Ping Tang; Xiaobin Liang; Ken Nakajima; Yuezhen Bin (Chemical Engineering Journal, 2025)

A novel CRISPR-driven Fe SANs-sensitized hydrogel biosensor for ultrasensitive detection of microcystin synthetase gene E (mcyE) and early warning of microcystin-LR - Pian Wu; Heng Dai; Jun Liu; Yuan Tian; Xiaolong Qu; Zongwu Meng; Tianhan Kai; Ping Ding (Chemical Engineering Journal, 2025)

MSVnet: A multi-scale and multi-view discriminator for fish detection in unseen domain - Tianyi Liao; Yang Qu; Yinyi Chen; Ping Zhong; Junyan Tan (Aquaculture, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Spent mushroom substrate amendment induces suppressiveness against cucumber Fusarium wilt through changes in the rhizosphere microbiome - Yuanhang Qu; Tiancong Liu; Lihong Dong; Lemeng Dong; Zhenhe Su; Harro Bouwmeester; Qinggang Guo; Ping Ma (Plant and Soil, 2025)

A sensitive humidity-responsive actuator based on dispersing graphene oxide into chitosan- sodium alginate nanofibers - Yonghao Chen; Meijie Qu; Chenshen Liu; Shuhui Li; Xincheng Wang; Daixuan Gong; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2025)

Nacre-inspired bacteriostatic polymer film with ultrastrong and high barrier properties by self-assembly in the cold solid-state - Senhao Zhang; Ziming Luo; Guangmei Yang; Mingjin Liu; Shun Liu; Jin-Ping Qu (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Promotional activity of an uncharacterized protein Bm0979 on Nosema bombycis in silkworm, bombyx mori - Yujia Fang; Qiong Yu; Wenzhe Chen; Zhenghao Han; Qingsheng Qu; Zhenwei Jia; Shidong Jiang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Asia-Pacific Entomology, 2025)

Corrigendum to “A high-sensitive PDMS-based sensor with a wide sensing range by fabricating refined and reconstructable conductive network” [Chem. Eng. J. 507 (2025) 160626] - Shuaishuai Zhou; Huanhuan Zhang; Qian Chen; Qing-wen Yuan; Sen-hao Zhang; Nannan Bao; Jin-Ping Qu (Chemical Engineering Journal, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

The three-dimensional electrocatalytic oxidation system for refractory organic wastewater remediations: Mechanisms, electrode material and applications - Linjin Li; Yaoze Wang; Guangfei Qu; Ping Lu; Ting Zhang; Jun Wang; Minhua Cheng; Nanqi Ren; Yuanchuan Ren (Journal of Environmental Chemical Engineering, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Hydrochemical insights into spatiotemporal characteristics of groundwater salinization and health risk assessment of fluoride in the south bank of Yellow River irrigation area, Northwest China - Muhan Li; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Rina Wu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Environmental Geochemistry and Health, 2025)

RNA Binding Protein IGF2BP3 Rehabilitates Glycolysis of Vascular Endothelial Cells to Protect the ox-LDL-induced Cellular Injury via Stabilizing LDHA mRNA - Xing-Chun Mo; Ping Lu; Qu-Cheng Wei; Xiao-Jing Yang (Cell Biochemistry and Biophysics, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Optimized fertilization for effective suppression of soil-borne disease: Differential effects on bulk and rhizosphere soils - Xiaojing Qu; Jun Zhang; Yu Duan; Wei Zhou; Ping He (Field Crops Research, 2025)

A High-Sensitive PDMS-Based sensor with a Wide Sensing Range by fabricating refined and reconstructable conductive network - Shuaishuai Zhou; Huanhuan Zhang; Qian Chen; Qing-wen Yuan; Sen-hao Zhang; Nannan Bao; Jin-Ping Qu (Chemical Engineering Journal, 2025)

Engineering electron delocalization of ultrathin covalent organic framework nanosheets to elevate photocatalytic hydrogen evolution in seawater - Qihong Yue; Zhihao Zhang; Xiaoling Liu; Chenjie Zhu; Ying Wen; Ping Fu; Qizhi Hu; Xinhao Qu; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2025)

Underlying the early signaling and gene expression of Pleurotus ostreatus mycelia during injury response - Jiachun Zhu; Jiaqi Sun; Huiping Li; Ping Xu; Lin Ma; Qiang Wang; Keping Chen; Shaoxuan Qu (World Journal of Microbiology and Biotechnology, 2025)

The dark activity of Arabidopsis blue-light receptor CRY2 - Gao-Ping Qu; Zeru Zhang; Chentao Lin (Science China Life Sciences, 2025)

Study on the feasibility of buckwheat as a trap plant for flower thrips (Frankliniella intonsa) in sunflower field - Hui Qu; Jing Chang; Ze-Run Chuai; Wen-Bing Zhang; Jian Zhang; Jun Zhao; Hai-Ping Li (Journal of Pest Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Spatial and anchoring effects of zirconia-doped 3D scaffolds for stable zinc anodes - Jinqiu Ye; Tiancheng Ge; Xin Qu; Mohamedazeem M. Mohideen; Ce Wang; Ping Hu; Yong Liu (Chemical Engineering Journal, 2025)

Associations of Exposure to 56 Serum Trace Elements with the Prevalence and Severity of Acute Myocardial Infarction: Omics, Mixture, and Mediation Analysis - Zhonghua Sun; Ying Xu; Ying Liu; Xinyu Tao; Ping Zhou; Han Feng; Yangyang Weng; Xiang Lu; Jun Wu; Yongyue Wei; Chen Qu; Zhengxia Liu (Biological Trace Element Research, 2025)

Self-enhancement of food packaging film based on regulable microstructure evolution via circumfluent synergistic blow molding - Senhao Zhang; Tianyuan Gao; Zexiang Xie; Shuaishuai Zhou; Cong Fang; Zhikun Gao; Haowei Jiang; Jin-Ping Qu (Food Packaging and Shelf Life, 2025)

Recent advancements in novel quantum 2D layered materials hybrid photodetectors from IR to THz: From principles to performance enhancement strategies - Muhammad Abdullah; Muhammad Younis; Muhammad Tahir Sohail; Muhammad Asif; Yin Jinde; Yan Peiguang; Qu Junle; Zheng Ping (Chemical Engineering Journal, 2025)

Insight into metabolomics analysis of large yellow croaker liver (Larimichthys crocea) during packaging bag transport - Haofeng Sun; Fukun Gui; Dejun Feng; Ping Wang; Xiaoyu Qu; Shuai Niu; Guangyang Zhang (Aquaculture International, 2025)

Metal oxide-molten salt catalyzed pyrolysis: Improving the energy conversion efficiency of wheat straw - Youxiao Xu; Guangfei Qu; Zhoupeng Yan; Huanhuan Wu; Ping Ning (Process Safety and Environmental Protection, 2024)

Physicochemical evaluation, structural characterization, in vitro and in vivo bioactivities of water-soluble polysaccharides from Luobuma (Apocynum L.) tea - Aminu Shehu Abubakar; Bilal Ahmad; Nabi Ahmad; Liangliang Liu; Bin Liu; Yatong Qu; Jikang Chen; Ping Chen; Haohan Zhao; Jia Chen; Kunmei Chen; Gang Gao; et al. (Food Chemistry, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Association of Oxidative Stress on Cognitive Function: A Bidirectional Mendelian Randomisation Study - Zhixing Fan; Chaojun Yang; Xiaoling Qu; Jing Zhang; Hui Wu; Ying Yang; Yifan Huang; Ping Zeng; Zujin Xiang; Jian Yang (Molecular Neurobiology, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

The genome survey of male and female Hapalogenys analis - Kai Liu; Yin-Quan Qu; Hui-Lai Shi; Hong-Ling Ping; Tian-Xiang Gao (Frontiers in Marine Science, 2024)
Effectively assessing the basic genomic information of a species is fundamental for conducting molecular research and provides a foundation for constructing whole-genome maps. Hapalogenys analis is a temperate and tropical nearshore marine fish in China’s coastal waters, with significant economic value and high aquaculture potential. However, the genomic differences between male and female individuals of this species are not yet apparent. This study conducted whole-genome survey analyses on male and female H. analis to provide basic genomic information. According to K-mer analysis, the genome sizes of female and male fish were 436.24 Mb and 493.21 Mb. The heterozygosity rates were 0.58% for females and 0.23% for males. The proportion of repetitive sequences of female and male fish were 42.95% and 51.20%. The GC content of the genomes was 43.30% for female and 43.20% for male. The sizes of the assembled genomes were 589.18 Mb for female and 592.02 Mb for male, with N50 lengths of 3,135 bp and 3,041 bp, respectively. SSR screening results showed that 959,447 and 894,158 SSR sequences were detected in the genomes of female and male, respectively. The lengths of the assembled mitochondrial genome sequences were 19,755 bp for female and 19,754 bp for male, each containing 38 genes. Among these mitochondrial sequences, 13 protein-coding genes were identified, including 7 NADH dehydrogenase, 3 cytochrome c oxidase, 1 cytochrome b, and 2 ATP synthase genes. Both sequences contained 23 tRNA genes and 2 rRNA genes. This study provides a theoretical basis for constructing a high-quality whole genome of H. analis and valuable data for subsequent molecular breeding research.

Highly efficient removal and real-time visual detection of fluoride ions using ratiometric CAU-10-NH2@RhB: Probe design, sensing performance, and practical applications - Ping Ju; Wenhui Lu; Guixue Zhang; Shuping Wang; Anzhang Li; Qingxiang Zhang; Long Jiang; Ensheng Zhang; Fengli Qu (Journal of Hazardous Materials, 2024)

Reclamation alters evapotranspiration and its biophysical controls in a meadow grassland on the Mongolian Plateau - Xiaobing Dong; Gang Dong; Jingyan Chen; Tsegaye Gemechu Legesse; Shicheng Jiang; Muhammad Adnan Akram; Lu-Ping Qu; Lulu Wang; Jianming Deng; Changliang Shao (Journal of Environmental Management, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Research on temperature measurement model of loose coal considering humidity using acoustic wave method - Gao-yang Qu; Jun Deng; Shuai-jing Ren; Cai-ping Wang; Ze-yang Song; Jin-rui Wang; Yu Xu; Xia-qi Zhao (Fuel, 2024)

Commensal bacteria in raw milk, the reservoirs for antibiotic resistance genes during cold chain transportation - Ping Wang; Lijiao Liang; Tianming Qu; Xiaomei Zhao; Yongsheng Zhao; Qinglong Ji; Ying Chen (Food Control, 2024)

Renewable hemicellulose-based materials for value-added applications - Guangfu Liao; Enhui Sun; E.B. Gueguim Kana; Hongying Huang; Isaac A. Sanusi; Ping Qu; Hongmei Jin; Jun Liu; Li Shuai (Carbohydrate Polymers, 2024)

Soil environmental anomalies dominate the responses of net ecosystem productivity to heatwaves in three Mongolian grasslands - Lu-Ping Qu; Gang Dong; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Jingyan Chen; Shicheng Jiang; Ochirbat Batkhishig; Tsegaye Gemechu Legesse; Xiaoping Xin; Changliang Shao (Science of The Total Environment, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Patterns and drivers of organic carbon in hydromorphic soils across inland aquatic-terrestrial ecotones at the global scale - Yiguo Ran; Peng Wang; Fei Ye; Junfeng Qu; Yang Ning; Yanshuo Zhang; Zhaofei Wen; Shengjun Wu; Ping Huang (CATENA, 2024)

SLCOBNet: Shrimp larvae counting network with overlapping splitting and Bayesian-DM-count loss - Yang Qu; Sheng Jiang; Daoliang Li; Ping Zhong; Zhencai Shen (Biosystems Engineering, 2024)

New geographical records and molecular investigation of the ciliate Spirostomum - Sheng-Bo Zhou; Zhi-Yu Zhao; Ping Guan; Bo Qu (Protist, 2024)

Complete genome sequence of Kushneria phosphatilytica YCWA18T reveals the P-solubilizing activity of the genus Kushneria - Guang-xun Du; Wen-sheng Yu; Ji-kun Su; Guo-chong Liu; Ping Gao; Xu-guang Hong; Ling-yun Qu (Marine Genomics, 2024)

A novel process for efficient and selective recovery of potassium from phosphorus electrostatic precipitator dust using ionic liquids - Keheng Pan; Chi Zhao; Guangfei Qu; Yuqi Liang; Changfei Guo; Ping Ning (Journal of Cleaner Production, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Key residues involved in the interaction between chlorpyrifos and a chemosensory protein in Rhopalosiphum padi: Implication for tracking chemical residues via insect olfactory proteins - Ping Gao; Junjie Tan; Xiong Peng; Mingjing Qu; Maohua Chen (Science of The Total Environment, 2024)

Metagenomic profiles of the antimicrobial resistance in traditional Chinese fermented meat products: Core resistome and co-occurrence patterns - Tianming Qu; Ping Wang; Xiaomei Zhao; Lijiao Liang; Qinglong Ji; Yiqiang Ge; Ying Chen (International Journal of Food Microbiology, 2024)

Deep learning network with new weighting strategy for ISAR image enhancement - Ping Cheng; Xinmiao Xu; Xinkai Yang; Yunqing Nie; Weiyang Chen; Zhiyu Qu; Jiaqun Zhao (International Journal of Remote Sensing, 2024)

Tailoring raloxifene into single-component molecular crystals possessing multilevel stimuli-responsive room-temperature phosphorescence - Zhichao Pan; Jinming Song; Shasha Zhang; Ping Zeng; Ju Mei; Da-Hui Qu (Science Bulletin, 2024)

Numerical study on dynamic buckling of a cylindrical shell subjected to underwater explosion - Chen-Xing Qu; Shao-Fei Ren; Shi-Ping Wang; Qiang Zhong (Ocean Engineering, 2024)

A comprehensive assessment indicator of the water-energy-food nexus system based on the material consumption relationship - Lingang Hao; Jingjie Yu; Ping Wang; Chunhui Han; Boris Gojenko; Bo Qu; Enhui Jiang; Sherzod Muminov (Journal of Hydrology, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Environmental fate of benzotriazole 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV-328) on the surface of plastic films in soil: Migration and phototransformation - Nannan Wu; Boying Liu; Ying Zhang; Ahmed A. Allam; Ahmed Rady; Naif G. Altoom; Afzal ahmed Dar; Ruijuan Qu; Zunyao Wang; Ping Sun (Journal of Environmental Chemical Engineering, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Urea reduces the sustainability of soil Cd immobilization by upregulating the expression of AmSTOP1 and AmMATE genes in edible amaranth roots - Fo-Peng Wang; Jun-Feng Wang; Tao He; Ping Tian; Xiao-Qian Song; Qu-Sheng Li (Environmental Pollution, 2024)

Multifunctional bamboo-based composites in-situ coated with graphene via continuous steam explosion - Yunfeng Zhao; Senhao Zhang; Mingjin Liu; Qian Chen; Yingpei Zhang; Zhao-Xia Huang; Jin-Ping Qu (Chemical Engineering Journal, 2024)

Correlation of Gut Microbiota with Children Obesity and Weight Loss - Li-Jun Peng; Yan-Ping Chen; Fang Qu; Yan Zhong; Zhi-Sheng Jiang (Indian Journal of Microbiology, 2024)

Forecasting and early warning of bridge monitoring information based on a multivariate time series ARDL model - Bing Qu; Yaolong Huang; Jieqing She; Ping Liao; Xiuying Lai (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Unravelling the nature of the active species as well as the Mn doping effect over gamma-Al2O3 catalyst for eliminating AsH3 and PH3 - Bowen Xu; Jiaxin Qu; Xueqian Wang; Langlang Wang; Yu Pu; Ping Ning; Yibing Xie; Yixing Ma; Qiang Ma (Journal of Environmental Sciences, 2024)

Clinico-pathological and gene features of 15 nemaline myopathy patients from a single Chinese neuromuscular center - Lv Haidong; Liu Yin; Chen Ping; Zheng Xianzhao; Qian Qi; Ma Xiaoli; Lv Zheng; Cui Wenhao; Zhou Yaguang; Qu Qianqian (Acta Neurologica Belgica, 2024)
Background Nemaline myopathy, the most common of the congenital myopathies, is caused by various genetic mutations. In this study, we attempted to investigate the clinical features, muscle pathology and genetic features of 15 patients with nemaline myopathy. Results Among the 15 patients, there were 9 (60.00%) males and 6 (40.00%) females, and 9 (60.00%) of them came from three families respectively. The age of seeing a doctor ranged from 9 to 52 years old, the age of onset was from 5 to 23 years old, and the duration of disease ranged from 3 to 35 years. Ten out of the 15 patients had high arched palate and elongated face. Only one patient had mild respiratory muscle involvement and none had dysphagia. Muscle biopsies were performed in 9 out of the 15 patients. Pathologically, muscle fibers of different sizes, atrophic muscle fibers and compensatory hypertrophic fibers could be found, and occasionally degenerated and necrotic muscle fibers were observed. Different degrees of nemaline bodies aggregation could be seen in all 9 patients. The distribution of type I and type II muscle fibers were significantly abnormal in patients with nemaline myopathy caused by NEB gene, however, it was basically normal in patients with nemaline myopathy caused by TPM3 gene and ACTA1 gene. Electron microscopic analysis of 6 patients showed that nemaline bodies aggregated between myofibrils were found in 5(83.33%) cases, and most of them were located near the Z band, but no intranuclear rods were found. The gene analysis of 15 NM patients showed that three NM-related genes were harbored, including 11 (73.33%) patients with NEB, 3 (20.00%) patients with TPM3, and 1 (6.67%) patient with ACTA1, respectively. A total of 12 mutation sites were identified and included 10 (83.33%) mutations in exon and 2(16.67%) mutations in intron. Conclusions The clinical phenotype of nemaline myopathy is highly heterogeneous. Muscle pathology shows that nemaline bodies aggregation is an important feature for the diagnosis of NM. NEB is the most frequent causative gene in this cohort. The splicing mutation, c.21522 + 3A > G may be the hotspot mutation of the NEB gene in Chinese NM patients.

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Chitin nanocrystals as natural gel modifier for yielding stronger acid-induced soy protein isolate gel - Qin Zhang; Ping Sun; Zejian Xu; Wenwen Qu; Yan Zhang; Xiaonan Sui (Carbohydrate Polymers, 2024)

Mechanism study on a novel Cu/Fe co-catalyzed heterogeneous particle mediated activation of hydrogen peroxide for efficient degradation of cyanides - Xiuping Chen; Ting Zhang; Guangfei Qu; Yuanchuan Ren; Zuoliang Wang; Jun Wang; Ping Lu; Minhua Cheng; Xiaomei Chu (Journal of Water Process Engineering, 2023)

High fire safety thermal protective composite aerogel with efficient thermal insulation and reversible fire warning performance for firefighting clothing - Zhicai Yu; Yuhang Wan; Yi Qin; Qing jiang; Jin-Ping Guan; Xian-Wei Cheng; Xiaochun Wang; Shengnan Ouyang; Xueru Qu; Zhenyu Zhu; Jinfeng Wang; Hualing He (Chemical Engineering Journal, 2023)

CRISPR/Cas-based gene editing in therapeutic strategies for beta-thalassemia - Shujun Zeng; Shuangyin Lei; Chao Qu; Yue Wang; Shuzhi Teng; Ping Huang (Human Genetics, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Bioassay and Whole-Genome Analysis of Bacillus velezensis FIO1408, a Biocontrol Agent Against Pathogenic Bacteria in Aquaculture - Wenhao Huang; Lingyun Qu; Ping Gao; Guangxun Du (Current Microbiology, 2023)

QbD-Guided Traditional Chinese Medicine Manufacturing Process: Development and Optimization of Fluid-Bed Granulation and Drying Processes for Xiaochaihu Capsules - Kaixuan Teng; Hao Fu; Gelin Wu; Ping Gong; Yongjian Xie; Peng Zhou; Xingchu Gong; Haibin Qu (AAPS PharmSciTech, 2023)

Deciphering spatio-seasonal patterns, driving forces, and human health risks of nitrate and fluoride enriched water bodies in the Inner Mongolia Reaches of the Yellow River Basin, China - Shen Qu; Yanyun Luo; Limin Duan; Sensen Pei; Ping Miao; Chenyu Wang; Tingxi Liu; Ruihong Yu (Environmental Science and Pollution Research, 2023)

Simultaneous electrochemical detection of dimethyl bisphenol A and bisphenol A using a novel Pt@SWCNTs-MXene-rGO modified screen-printed sensor - Guangfei Qu; Yun Zhang; Junhong Zhou; Huimin Tang; Wei Ji; Zhoupeng Yan; Keheng Pan; Ping Ning (Chemosphere, 2023)

Study on the mechanism of rapid degradation of Rhodamine B with Fe/Cu@antimony tailing nano catalytic particle electrode in a three dimensional electrochemical reactor - Yuanchuan Ren; Ping Lu; Guangfei Qu; Ping Ning; Nanqi Ren; Jun Wang; Fenghui Wu; Xiuping Chen; Zuoliang Wang; Ting Zhang; Minhua Cheng; Xiaomei Chu (Water Research, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

The legacy effects of soil types on carbon content are erased by extreme flooding stress in a water-level drawdown zone - Yiguo Ran; Shengjun Wu; Yi Jiang; Junfeng Qu; Imali Kaushalya Herath; Ping Huang (CATENA, 2023)

A strain of Vibrio alginolyticus isolated from Azumapecten farreri and its pathogenic mechanism using CRISPR-Cas9 technology - Jingxue Ma; Peiyu Zhang; Minggang Zheng; Bo Wang; Ping Gao; Lingyun Qu; Fengrong Zheng (Biotechnology Letters, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Nitrogen-coordinated cobalt embedded in hollow carbon polyhedron for catalytic ozonation of odor CH3SH at ambient temperature - Hailin Wen; Wei Qu; Muke Lin; Lingzhi Zhou; Xuexia Guo; Ping Ma; Taoli Wu; Huinan Zhao; Tao Zhong; Chun He (Chemical Engineering Journal, 2023)

Self-checking dual-modal aptasensor based on hybrid Z-scheme heterostructure of Zn-defective CdS/ZnS for oxytetracycline detection - Pei Song; Ping Qu; Min Wang; Ai-Jun Wang; Yadong Xue; Li-Ping Mei; Jiu-Ju Feng (Analytica Chimica Acta, 2023)

Interannual variation of midsummer precipitation in the middle reaches of Yarlung Zangbo River and its possible mechanisms - Cheng Yang; Qu Chi; Shunwu Zhou; Ping Wu; Lunzhu Danzeng; Yang Sun (International Journal of Climatology, 2023)
Hydroclimatic process in Yarlung Zangbo River (YZR) plays a critical role in the water cycle of the whole Tibetan Plateau (TP), but there is a lack of understanding about it due to restrictive conditions. In this study, we further investigate the interannual variation characteristics and possible factors of midsummer (July–August) precipitation in the middle reaches of YZR (MYZR) based on the monthly precipitation data from four stations (Lhasa, Xigaze, Tsedang and Gyangze) in the Inner TP and ERA5 reanalysis dataset for the years 1961–2017. The results suggest that precipitation shows no obvious linear trend during the research period but is dominated by interannual oscillation with evident cycles of 3 years. Meanwhile, the interannual variation of precipitation is related to local changes of water vapour budget. The anomalous anticyclones over the Indian Peninsula‐Southeast Asia continuously transport water vapour from the western Pacific, South China Sea and Bay of Bengal (BOB) to the TP. Simultaneously, both the monsoon low and South Asia high in southern TP provide dynamic conditions for the convergence and uplift of water vapour.

Hexachloroplatinic(IV)-GO colloids as ideal electrodes modification materials for electrochemical sensing, HER and OER - Guangfei Qu; Junhong Zhou; Wei Ji; Huimin Tang; Kunling Wei; Yun Zhang; Keheng Pan; Ping Ning (Chemical Engineering Journal, 2023)

Efficient fabrication of poly(vinylidene fluoride)/graphene composite actuators with robust superhydrophobicity and excellent photothermal performance for controllable light-driven motion - Xiao-wei Ning; Ting Wu; Yu Du; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Degradation of PCB77 in spiked soils by ferrous sulfide-activated persulfate combined with potassium permanganate - Yue Bu; Nannan Wu; Yumeng Qi; Junyan Wei; Xiaosheng Tang; Ahmed A Allam; Ping Sun; Zunyao Wang; Ruijuan Qu (Chemical Engineering Journal, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

HCl-assisted KOH activated Chinese medicine residue biochar as a new method to improve the purification capacity of lead-containing wastewater: Experimental and mechanism studies - Yuanchuan Ren; Yuyi Yang; Guangfei Qu; Ping Ning; Nanqi Ren; Xiuping Chen; Zuoliang Wang; Yan Hu (Sustainable Chemistry and Pharmacy, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Highly efficient nitrobenzene removal by coupling electrochemical filtration with a microbial electrolysis cell - Jingjing Guo; Kuiling Li; Zhiyong Wang; Dan Qu; Ping Dang; Jun Wang (Journal of Environmental Chemical Engineering, 2023)

Bio-based tannic acid as a raw material for membrane surface modification - Shiyu Zhou; Yang Qu; Bowen Yang; Qiang Zhang; Jin Wang; Yamei Lin; Zhong Chen; Guo-Ping Lu (Desalination, 2023)

A Janus-type hygroscopic hydrogel for reusable robust dehumidification and efficient solar thermal desorption - Yingying Chen; Weilong Zhou; Congyuan Zhang; Xiangmin Feng; Yonghong Deng; Xinchang Chen; Heng Xie; Ting Wu; Jin-ping Qu (Chemical Engineering Journal, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Water evaporation induced in-situ interfacial compatibilization for all-natural and high-strength straw-fiber/starch composites - Ying-Pei Zhang; Jin Wang; Kang-Wei Xia; Yun-Feng Zhao; Qing-Wen Yuan; Zhao-Xia Huang; Yanhong Feng; Jin-Ping Qu (Carbohydrate Polymers, 2023)

Single-base resolution mapping of 2′-O-methylation sites by an exoribonuclease-enriched chemical method - Ping Zhang; Junhong Huang; Wujian Zheng; Lifan Chen; Shurong Liu; Anrui Liu; Jiayi Ye; Jie Zhou; Zhirong Chen; Qiaojuan Huang; Shun Liu; Keren Zhou; et al. (Science China Life Sciences, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Hydrochemical and isotopic fingerprints of groundwater origin and evolution in the Urangulan River basin, China's Loess Plateau - Shen Qu; Limin Duan; Hairu Mao; Chenyu Wang; Xiangyang Liang; Ankun Luo; Lei Huang; Ruihong Yu; Ping Miao; Yuanzhen Zhao (Science of The Total Environment, 2023)

Deciphering the microbial community tolerance mechanism and alteration of antibiotic resistance genes during chloramphenicol wastewater treatment - Jia Zhou; Yan Chen; Wan-Xia Li; Jian-Hang Qu; Tian Chen; Yi-Ping Wang; Ning-Yu Geng (International Biodeterioration & Biodegradation, 2023)

Gas-in-place and its influence factors of the upper Paleozoic coal-bearing shale in the Qinshui Basin, China - Chengang Lu; Ping Gao; Gang Li; Yue Feng; Xiaorong Qu; Yufei Su; Xianming Xiao (Frontiers of Earth Science, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Fabrication of outstanding mechanical performance engineered poly (lactic acid)/thermoplastic poly(ester)urethane in-situ nanofiber composites with a large-scale industrial innovation methodology - Yue He; Cong Fang; Wen-Hua Xu; Ling-Cao Tan; Sen Qin; Xiao-Chun Yin; Yan-Hong Feng; Chul B. Park; Jin-Ping Qu (Chemical Engineering Journal, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Design of Control System for Multistage Distillation Seawater Desalination Device Driven by Photovoltaic-Thermal - Jiaqi Yan; Chengjun Qiu; Yuangan Wang; Ning Wu; Wei Qu; Yuan Zhuang; Guohui Yan; Ping Wang; Ruoyu Zhang; Yirou Yan; Ruonan Deng; Jiuqiang Luo; et al. (Journal of Marine Science and Engineering, 2023)
This research proposes a seawater desalination system driven by photovoltaic and solar thermal energy for remote regions such as islands and seaside villages where fresh water is not accessible. The performance of this system is demonstrated through experiments, and the main concerns are the output of the photovoltaic power generation system, power quantity, water yield, and the loads under different solar irradiance and temperature. In this system, a PLC is used as the controller to adjust the water pump by the collection and processing of sensor data. A load switching time system is designed to select different operating schemes under different environments in order to save energy. The control method of this system is developed to ensure that the photovoltaic power generation system does not undervoltage while maintaining the normal operation of the desalination system. An improved Perturbation and Observation (P&O) algorithm is also proposed as a new Maximum Point Power Tracking (MPPT) method to solve the problem of misjudgment and oscillation after tracking the maximum power point (MPP) in the traditional P&O algorithm. The simulation test in the MATLAB/Simulink environment shows that when external irradiance changes, the improved P&O algorithm can track the MPP faster than the traditional P&O algorithm, and the amplitude of oscillation on the MPP is smaller. The hardware experiments show that this system can operate stably and flexibly, and it is capable of producing 5.18 kWh of electric energy and 335.81 kg of freshwater per day. The maximum yield of the unit can reach 565.75 kg per day and the maximum daily power generation is 8.12 kWh.

Nano Biomass Material functionalized by β-CD@Ce(NO)3 as a high performance adsorbent to removal of fluorine from wastewater - Yuanchuan Ren; Ping Ning; Guangfei Qu; Nanqi Ren; Fenghui Wu; Yuyi Yang; Xiuping Chen; Zuoliang Wang; Yan Hu (Chemosphere, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Distinguishing the determinative landscape factors influencing the spatial variation of soil quality in Chongming Island, China - Yubing Qu; Yuan Chi; Jianhua Gao; Xuejian Ma; Ya Ping Wang (Journal of Coastal Conservation, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Degradation mechanism of HCN by electrochemically coupled copper-loaded magnetic nanoparticles in a liquid phase pseudo-homogeneous system - Guangfei Qu; Wei Ji; Junyan Li; Shuaiyu Liang; Zhishuncheng Li; Huimin Tang; Junhong Zhou; Ping Ning (Environmental Science and Pollution Research, 2022)

Probabilistic prediction of the spatial distribution of potential key blocks during tunnel surrounding rock excavation - Peng He; Li-ping Li; Gang Wang; Fei Xu; Shang-qu Sun (Natural Hazards, 2022)

Hydroxysafflor yellow A can improve depressive behavior by inhibiting hippocampal inflammation and oxidative stress through regulating HPA axis - Zhiqiang Liu; Yongzhou Zou; Min He; Ping Yang; Xinhui Qu; Lijun Xu (Journal of Biosciences, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Microporous modified atmosphere packaging to extend shelf life of fresh foods: A review - Ping Qu; Min Zhang; Kai Fan; Zhimei Guo (Critical Reviews in Food Science and Nutrition, 2022)

Integration of metabolomics and transcriptomics revealed the biosynthetic mechanism of anti-parasitic compounds in Salinivibrio proteolyticus strain YCSC6 - Guangxun Du; Lingyun Qu; Ping Gao; Wenhao Huang; Chenghua Li; Dewen Ding (Journal of Oceanology and Limnology, 2022)

Ocean salinity indices of interannual modes in the tropical Pacific - Jianwei Chi; Tangdong Qu; Yan Du; Jifeng Qi; Ping Shi (Climate Dynamics, 2022)
This study investigates the interannual modes of the tropical Pacific using salinity from observations, ocean reanalysis output and CMIP6 products. Here we propose two indices of sea surface salinity (SSS), a monopole mode and a dipole mode, to identify the El Niño—South Oscillation (ENSO) and its diversity, respectively. The monopole mode is primarily controlled by atmospheric forcing, namely, the enhanced precipitation that induces negative SSS anomalies across nearly the entire tropical Pacific. The dipole mode is mainly forced by oceanic dynamics, with zonal current transporting fresh water from the western fresh pool into the western-central and salty water from the subtropics into the eastern tropical Pacific. Under a global warming condition, an increase in the monopole and dipole mode variance indicates an increase in both the central and eastern Pacific El Niño variability. The increase in central Pacific El Niño variability is largely due to enhanced vertical stratification during global warming in the upper layer, with intensified zonal advection. An eastern Pacific El Niño-like warming pattern contributes to the increase in eastern Pacific El Niño, with enhanced precipitation over the central-eastern tropical Pacific.

Responses of ecosystem respiration, methane uptake and nitrous oxide emission to drought in a temperate desert steppe - Ping Yue; Xiaoan Zuo; Kaihui Li; Xiangyun Li; Shaokun Wang; Xujun Ma; Hao Qu; Min Chen; Liangxu Liu; Tom Misselbrook; Qiang Yu (Plant and Soil, 2021)

miR-140-3p regulates the osteogenic differentiation ability of bone marrow mesenchymal stem cells by targeting spred2-mediated autophagy - Ping Liu; Yan Zhuang; Binfei Zhang; Hai Huang; Pengfei Wang; Hu Wang; Yuxuan Cong; Shuangwei Qu; Kun Zhang; Xing Wei (Molecular and Cellular Biochemistry, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Functional analysis of indole 3-hexanoic acid as a novel auxin from Arabidopsis thaliana - Ping Song; Hui Xu; Jixiu Zhang; Huatao Chen; Li Li; Yana Qu; Feng Lin; Qun Zhang (Planta, 2021)

Aberrant activity within auditory network is associated with psychiatric comorbidities in interictal migraineurs without aura - Heng-Le Wei; Yu-Chen Chen; Yu-Sheng Yu; Xi Guo; Gang-Ping Zhou; Qing-Qing Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Both carbon sequestration and yield are related to particulate organic carbon stability affected by organic amendment origins in mollisol - Xiaojing Qu; Xiaohan Wang; Jinggui Wu; Ping He (Journal of Soils and Sediments, 2021)

Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress - Huirong Lv; Yanli Liu; Haidong Li; Xiaolong Yin; Ping Wang; Xiaoyu Qu; Yang Gao; Weiye Li; Zhangjie Chu (Frontiers in Marine Science, 2021)
The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for 3 days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8 from 12°C; T2 represents the group that sampled when the fish had been kept at 8°C for 3 days; T3 represents the group sampled when the water temperature was increased to 12 from 8°C. The antioxidant abilities of the liver, muscle, and intestine of large yellow croaker at different temperatures and times were determined, and the expression of HSP70 and HSP90 in the liver as well as the changes in intestinal microbiota were investigated. The results showed that the activities of SOD, CAT, GSH-Px, and MDA content increased significantly when the water temperature decreased from 12 to 8°C, significantly higher than those in the control group. The gene expression levels of HSP70 and HSP90 in the liver of large yellow croaker significantly increased under low temperature stress and were significantly higher than those in the control group. The diversity and abundance of intestinal microbiota of large yellow croaker were altered when the water temperature was maintained at 8°C, although the change was not obvious. Proteobacteria, Firmicutes, and Bacteroidetes were the dominate phyla in both the 12 and 8°C groups, and the temperature variation did not change the functional pathways of the microbiota. In conclusion, the acute temperature variation affected the antioxidant ability and heat shock protein expression of large yellow croaker but did not affect the diversity or abundance of the intestinal microbiota. These results will provide a theoretical basis for studying the mechanisms of large yellow croaker overwintering and adaptation to low temperatures.

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Bacterial and archaeal communities in deep sea waters near the Ninetyeast Ridge in Indian Ocean - Ping Gao; Lingyun Qu; Guangxun Du; Qinsheng Wei; Xuelei Zhang; Guang Yang (Journal of Oceanology and Limnology, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Impaired functional connectivity of limbic system in migraine without aura - Heng-Le Wei; Jinan Chen; Yu-Chen Chen; Yu-Sheng Yu; Gang-Ping Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2020)

Correction to: Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Complete Genome Sequence of Strain YCSC6, a Marine Bacterium Isolated from Saturated Saltpan with Activity Against Uronema marinum - Guang Xun Du; Ling Yun Qu; Kun Shang; Ping Gao; De Wen Ding; Cheng Jun Sun (Current Microbiology, 2020)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Ciliate Uronema marinum is the causative agent of scuticociliatosis in farm raised turbot Scophthalmus maximus - Guangxun Du; Lingyun Qu; Kun Shang; Chengjun Sun; Chen Wang; Ping Gao (Journal of Oceanology and Limnology, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Inhibition of thymocyte autophagy-associated CD4+T thymopoiesis is involved in asthma susceptibility in mice exposed to caffeine prenatally - Han-xiao Liu; Hui-yi Yan; Wen Qu; Xiao Wen; Li-fang Hou; Wen-hao Zhao; Jie Ping (Archives of Toxicology, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Low-thermal remediation of mercury-contaminated soil and cultivation of treated soil - Ting Zhao; Zhi Yu; Junfang Zhang; Liya Qu; Ping Li (Environmental Science and Pollution Research, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Geissoschizine synthase controls flux in the formation of monoterpenoid indole alkaloids in a Catharanthus roseus mutant - Yang Qu; Antje M. K. Thamm; Matthew Czerwinski; Sayaka Masada; Kyung Hee Kim; Graham Jones; Ping Liang; Vincenzo De Luca (Planta, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Rockfall Hazard Assessment on Wangxia Rock Mass in Wushan (Chongqing, China) - Shang-qu Sun; Li-ping Li; Shu-cai Li; Qian-qing Zhang; Cong Hu (Geotechnical and Geological Engineering, 2017)

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part I: Model Formulation and Analytical Expressions - Ding Wang; Shou-Li Qu; Ping-Bo Ding; Qun Zhao (Pure and Applied Geophysics, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Arabidopsis phospholipase D alpha 1-derived phosphatidic acid regulates microtubule organization and cell development under microtubule-interacting drugs treatment - Qun Zhang; Yana Qu; Qing Wang; Ping Song; Peipei Wang; Qianru Jia; Jinhe Guo (Journal of Plant Research, 2017)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Prismatic and full-waveform joint inversion - Ying-Ming Qu; Zhen-Chun Li; Jian-Ping Huang; Jin-Li Li (Applied Geophysics, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

TIPE2 acts as a negative regulator linking NOD2 and inflammatory responses in myocardial ischemia/reperfusion injury - Hongyu Zhang; Tianfeng Zhu; Wenwen Liu; Xin Qu; Ye Chen; Ping Ren; Ziying Wang; Xinbing Wei; Yan Zhang; Fan Yi (Journal of Molecular Medicine, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Identification of QTLs associated with salt or alkaline tolerance at the seedling stage in rice under salt or alkaline stress - Jing-long Liang; Ying-ping Qu; Chun-gang Yang; Xiao-ding Ma; Gui-lan Cao; Zheng-wu Zhao; San-yuan Zhang; Tao Zhang; Long-zhi Han (Euphytica, 2015)

Equatorward shift of the South Asian high in response to anthropogenic forcing - Xia Qu; Gang Huang; Kaiming Hu; Shang-Ping Xie; Yan Du; Xiao-Tong Zheng; Lin Liu (Theoretical and Applied Climatology, 2015)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Infrasound Exposure Induces Apoptosis of Rat Cardiac Myocytes by Regulating the Expression of Apoptosis-Related Proteins - Zhao-Hui Pei; Bao-Ying Chen; Ru Tie; Hai-Feng Zhang; Ge Zhao; Ping Qu; Xiao-Xing Zhu; Miao-Zhang Zhu; Jun Yu (Cardiovascular Toxicology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

The distribution and expression of claudin-5 and occludin at the rat blood–optic nerve barrier after borneol treatment - Di Jin; Feng Wang; Lijun Qu; Zhituo Li; Lianhong Jin; Ping Liu; Xiaolin Xu; Hao Cui (Molecular Biology Reports, 2011)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Two novel cSNPs of weaver gene in Chinese indigenous goat and their associations with milk yield - Zhuanjian Li; Zhongqi Chen; Xianyong Lan; Liang Ma; Yujiao Qu; Yanli Liu; Mijie Li; Ping Wang; Fei Li; Hong Chen (Molecular Biology Reports, 2010)

In Silico Construction of a Protein Interaction Landscape for Nucleotide Excision Repair - Nancy Tran; Ping-Ping Qu; Dennis A. Simpson; Laura Lindsey-Boltz; Xiaojun Guan; Charles P. Schmitt; Joseph G. Ibrahim; William K. Kaufmann (Cell Biochemistry and Biophysics, 2009)

Localization of QTL for basal root thickness in japonica rice and effect of marker-assisted selection for a major QTL - Lifeng Liu; Ping Mu; Xueqin Li; Yanying Qu; Yi Wang; Zichao Li (Euphytica, 2008)

Mapping QTLs of root morphological traits at different growth stages in rice - Yanying Qu; Ping Mu; Hongliang Zhang; Charles Y. Chen; Yongming Gao; Yuxiu Tian; Feng Wen; Zichao Li (Genetica, 2008)

Biodecolorization of Azo Dye Acid Red B under High Salinity Condition - M. Salah Uddin; Jiti Zhou; Yuanyuan Qu; Jianbo Guo; Ping Wang; Li hong Zhao (Bulletin of Environmental Contamination and Toxicology, 2007)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

Root and vascular tissue-specific expression of glycine-rich protein AtGRP9 and its interaction with AtCAD5, a cinnamyl alcohol dehydrogenase, in Arabidopsis thaliana - An-Ping Chen; Nai-Qin Zhong; Zhan-Liang Qu; Fang Wang; Ning Liu; Gui-Xian Xia (Journal of Plant Research, 2007)

Trace Measurement of Phenothiazine Drugs in Tablets by Micellar-Enhanced Fluorophotometric Method - Gong-Jun Yang; Xi-Long Qu; Ming Shen; Qi-Shu Qu; Chen-Ying Wang; Ai-Ping Zhu; Xiao-Ya Hu (Journal of Fluorescence, 2007)

Ectopic expression of ThCYP1, a stress-responsive cyclophilin gene from Thellungiella halophila, confers salt tolerance in fission yeast and tobacco cells - An-Ping Chen; Gui-Ling Wang; Zhan-Liang Qu; Chun-Xia Lu; Ning Liu; Fang Wang; Gui-Xian Xia (Plant Cell Reports, 2007)

The ABI2-dependent abscisic acid signalling controls HrpN-induced drought tolerance in Arabidopsis - Hong-Ping Dong; Haiqin Yu; Zhilong Bao; Xiaojing Guo; Jianling Peng; Zhen Yao; Guangyong Chen; Shuping Qu; Hansong Dong (Planta, 2005)